Teaching English pronunciation by non-native teachers as seen by Slovak teachers - Bodorík Michal (Journal of Language and Cultural Education, 2017)
The English language has become the so called “world wide language” due to the fact that it is used globally in many spheres of everyday life - education, business, labour market, technology, tourism, travel and others. In Slovakia, the educational system supports schools in the acquisition of the language by granting more English classes per week, by financing textbook materials, by bridging teaching practice with research as well as making English a mandatory subject of school leaving exams.